Analytical Study of Handicraft Industries in Al-Zubair City - Ahmed Abdulqader Al-ramadan , Assist. Lect. Sundus (Basra studies journal, 2024)
Industry is the cornerstone of economic development for any country and a manifestation of cultural advancement. Handicraft industries are a subset of these industries, some of which are still present and active, while others have declined or disappeared due to their inability to keep up with modern developments in the industry, such as leather industries. This research delves into the concept of handicraft industries, encompassing eight industrial crafts distributed across six industrial branches, with a total workforce of 145 workers. The study examines the key factors that have facilitated the localization of these industries, their geographic distribution, and concentration in certain areas over others. It also addresses the challenges faced by these industries, which have hindered the development and led to the decline of many. The researcher proposes solutions that, if implemented, would contribute to the development and preservation of the remaining crafts in Al-Zubair City.